2005
DOI: 10.1002/j.1551-8833.2005.tb07453.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification potential curves: a new strategy for nitrification prevention

Abstract: In this article, nitrification potential curves are introduced as a possible operational strategy to prevent nitrification in chloraminated distribution systems. Nitrification potential curves are constructed based on the parameters that define growth and inactivation kinetics of ammoniaoxidizing bacteria in environments that contain chloramine and ammonia. To demonstrate the applicability of nitrification potential curves, long‐term, pilot‐scale studies that covered a range of chlorine‐to‐ammonia application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 23 publications
(33 reference statements)
2
41
0
Order By: Relevance
“…According to the nitrification poten-tial curves by Fleming et al [45], nitrification is prevented when the mass ratio of total chlorine and ammonia is above 8:1 mg Cl 2 : mg N. In our research, the total residual chlorine in the water supplied from the WTPs was 0.35 -0.4 mg…”
Section: Nitrificationsupporting
confidence: 49%
See 1 more Smart Citation
“…According to the nitrification poten-tial curves by Fleming et al [45], nitrification is prevented when the mass ratio of total chlorine and ammonia is above 8:1 mg Cl 2 : mg N. In our research, the total residual chlorine in the water supplied from the WTPs was 0.35 -0.4 mg…”
Section: Nitrificationsupporting
confidence: 49%
“…Fleming et al [45] calculated that below a theoretical threshold concentration of total residual chlorine of 1.6 mg…”
Section: Nitrificationmentioning
confidence: 99%
“…However, recent findings have shown that other species e e.g., Nitrosomonas oligotropha (Regan et al 2002), nitrifying Archaea (Hoefel et al, 2011), and heterotrophic nitrifiers (Daum et al, 1998) can be present and contribute to nitrification. The equation for BRC was implemented by Fleming et al (2005) and further modified by Sathasivan et al (2008) as follows: According to the biostability concept (Woolschlager et al, 2001) the regrowth of AOB can be prevented if the inactivation rate equals or exceeds the bacterial growth rate at each location within the distribution system (Sarker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These four pathways result in a complex scenario for whether or not N. europaea (or AOB in general) will be able to sustain themselves in the presence of monochloramine. Thus far, Pathways A, B, and C have been considered when developing conceptual models to understand the competing impacts of monochloramine inactivation and growth on ammonia in drinking water distribution systems, leading to growth versus inactivation models (e.g., Fleming et al, 2005;Schrantz et al, 2013;Speitel et al, 2011). One challenge to using these nitrification occurrence models is that N. europaea monochloramine inactivation studies have provided widely different estimates for inactivation rate constants based on the inactivation criterion selected.…”
Section: Introductionmentioning
confidence: 99%